63 Optimization of injected activities in 99mTc- Sestamibi myocardial perfusion tomoscintigraphy. (December 2018) - Joly, S.; Fontaine, J.; Verrecchia, E.; Retif, P.; Mahmoud, S. Ben
Abstract : Introduction: Optimization of radiopharmaceutical injected activities is an important issue for patient's radioprotection in nuclear cardiology. This study aims to compare two gamma-cameras from different generations, the first one using a parallel hole collimator (PHC), and the second one using a converging collimator (CC) focused on the heart area, in myocardial tomoscintigraphy. It allows highlighting which factors impact the scintigraphic image quality, in order to optimize the injected activities, taking into account these factors and the better sensitivity obtained with the CC camera. Methods: Two groups of patients had myocardial perfusion imaging, respectively with a PHC camera (PHC group, n = 154) and a CC camera (CC group, n = 46). The average sensitivity was defined as the ratio between the average number of counts detected per voxel in left ventricle and the total number of counts emitted during the whole exam. For both groups and for each patient the average sensitivity was calculated and compared to the population characteristics (weight, size, BMI). In the same time, a qualitative visual analysis was conducted by four nuclear physicians, for a sub-group of 15 patients from the PHC group. The scintigraphic images were noted on a scale going from 1 to 5, in order to define the minimal image quality adequate for reliable interpretation. An average sensitivity threshold was defined from the visual analysis, and a minimal injected activity was calculated depending on the patients' weight. Moreover, the sensitivity of each camera was experimentally measured on a phantom, and the sensitivity gain factor between the two devices was calculated. Results: The analysis realized on the PHC group showed a good correlation between the patients' weight and the exam average sensitivity. The exponential fit correlation coefficient was 0.83 ± 0.02. The same fit was also relevant for the CC group analysis, confirming the model reliability. The qualitative visual analysis helped to define an average sensitivity threshold of 4.82.10 −10 . From this threshold, the injected activities could be optimized depending on the patients' weight (Fig. 1). The CC camera sensitivity was measured 5 times greater than the PHC camera sensitivity. This sensitivity gap was taken into account to calculate the optimized average sensitivity on the CC camera. Finally, the global sensitivity gain factor was calculated depending on the patients' weight, up to 10 for the lowest weight patients. Conclusions: The CC camera brings an important sensitivity gain, allowing consequent reduction of injected activities. This preliminary study is a first step for the methodical optimization of injected activities, for the patients requiring a myocardial perfusion imaging.